Lessons from inter-disciplinary collaboration to mitigate SARS-CoV-2 transmission in schools, Ireland, 2020/2021, to inform health systems and multisectoral recovery - Naughton, Peter; Kelly, Ciara; White, Philippa; Kennedy, Elizabeth; Healy, Anne; Collins, Abigail; Ward, Mary (Frontiers in Public Health, 2023)
Introduction School closures associated with the COVID-19 pandemic resulted in the loss of educational and social supports for up to 1,000,000 students in Ireland and disproportionately affected students from lower socio-economic backgrounds. For the 2020/2021 school year, multisectoral and interdisciplinary “Schools Teams” were established within Public Health departments to maintain in-person education by minimizing transmission of SARS-CoV-2 in schools. This study aimed to describe this model and explore the experiences of Schools Team members in the East of Ireland to identify factors that influenced effective working that can be sustained in the context of health systems and multisectoral recovery. Methods Schools Teams were comprised of multidisciplinary staff from regional Public Health departments and redeployed staff from the Education sector. Governance rested with Public Health departments. All staff operated to nationally agreed protocols following training. The experiences of the East Schools Team members were explored through an online survey and semi-structured interviews. Results The survey response rate was 53/70 (75.7%). Participants reported clear channels of communication within the team (44, 83.0%), feeling comfortable in their role following training (43, 82.7%) and a positive team culture (51, 96.2%) as key facilitators of effective inter-disciplinary working. Insufficient administrative support and mixed messaging to schools were identified as barriers to efficient team collaboration. Discussion The Schools Team model illustrates the potential for multisectoral partnerships to effectively address complex public health priorities and contribute toward health system resilience to health threats. By recognizing and leveraging the ability of allied sectors such as the education sector, to contribute to public health goals, countries can move toward the kind of whole-of-government approach to health recognized as key to health system resilience. The strong links between the education and public health sectors developed through this collaboration could be extended and strengthened to more effectively pursue public health priorities in school settings. More broadly, mechanisms to support multisectoral working should be developed, expanding beyond reactive interventions to proactively address key health priorities and build resilience across health systems and communities. Such collaborations would promote healthier populations by promoting and encouraging a public health perspective among other sectors and embedding “health in all policies”.